Cold Acclimation for Enhancing the Cold Tolerance of Zebrafish Cells - Wang, Huamin; Wang, Ying; Niu, Minghui; Hu, Linghong; Chen, Liangbiao (Frontiers in Physiology, 2022)
Cold stress as an important threat facing the aquaculture industry is a common phenomenon in the life history of fish. The current research on the tolerance mechanism of fish cold stress is not perfectly developed. By using ZF4 cells as the research material, the process of short-term low temperature stress and long-term low temperature acclimation was applied to the cell, to explore the relevant molecular mechanisms of fish cold stress tolerance. The results showed that the cells aggregated into clumps under cold stress, and the proliferation rate decreased. Through research on the oxidative stress pathway, it is found that ROS content was increased under short-term cold stress, glutathione (GSH), catalase (CAT), superoxide dismutase (SOD) enzyme activity levels were changed. And the mitochondrial apoptosis pathway was activated and the level of apoptosis was increased. After 3 months of acclimatization at 18°C, ROS levels and apoptosis were decreased, and the body eliminated excess reactive oxygen free radicals and maintained balance. When the domesticated cells were placed at 13°C 5 days, compared with the non-domesticated group, the ROS level was lower and apoptosis was reduced, indicating that cold acclimation can improve the low temperature tolerance of the cells. Through the exploration of the mechanism of zebrafish cell cold stress, it lays the foundation for the study of the molecular mechanism of fish cold adaptation.